The Swedish budget 1980/81 (Stockholm : Ministry of Finance, 1980)
This eighteenth edition of The Swedish Budget contains a summary of the draft budget for the fiscal year 1980/81, with more detailed reviews of the main items of government expenditure. The economic policy statement and the budget statement are presented in an abbreviation form.
A summary published by the Ministry of Economic Affairs and the Ministry of the Budget.
rpm 20/02/2019
Ref.
Keywords: Budget; Economic history; Sweden